Profile identification and characterization of risk perceptions and preventive behaviors during the COVID-19 pandemic: a latent profile analysis - Ong, Yi Xuan (2023)
In a public health crisis, communication plays a vital role in making sure policies and recommendations from the government level get disseminated accurately to its people and is only considered as effective when the public accepts, supports, complies to, and engages in policies or behaves as per governments' recommendations. Adopting the multivariate audience segmentation strategy for health communication, this study uses a data-driven analytical method to (1) identify audience segments of public health crisis communication in Singapore based on knowledge, risk perception, emotional responses, and preventive behaviors; and (2) characterize each audience segment according to demographic factors, personality traits, information processing styles, and health information preferences. Results (N = 2033) from a web-based questionnaire executed in August 2021 have identified three audience segments: the less-concerned (n = 650), the risk-anxious (n = 142), and the risk-majority (n = 1,241). This study offers insights to how audiences of public health crisis communication perceive, process, and respond to information directed to them during the pandemic, thereby informing policy makers to tailor more targeted public health communication interventions in promoting positive attitude and behavior change.